Case Report: A family history of peanut allergy and hereditary alpha-tryptasemia - Chantran, Yannick; Renaudin, Hélène; Arock, Michel; Guiddir, Tamazoust; Nemni, Ariane (Frontiers in Allergy, 2024)
Context. Hereditary alpha-tryptasemia (HαT) is associated with elevated basal serum tryptase (bST) and has been associated with a higher risk of severe anaphylactic reactions in subjects with clonal mast cell disorders or IgE-mediated hymenoptera venom-induced anaphylaxis.The consequence of this genetic trait remains to be determined in other allergic diseases, and in food allergy in particular.Objectives. Here, we describe three cases of peanut allergy among siblings from a single family of four, two of them associated with HαT, and the other associated with tryptase wildtype genotype.Methods. TPSAB1/TPSB2 genotypes were determined by digital PCR. After the case description, we provide a review of the literature regarding bST levels and tryptase genotypes in anaphylaxis, with a particular focus on food allergy.. As compared to the sibling with conventional tryptase genotype, the two siblings with HαT presented lower peanut threshold at the initial oral food challenge, higher peanut skin prick test reactivity, higher levels of specific IgE to peanut, Ara h 2, and Ara h 6, and lower IgG4/IgE ratio after 10 years oral immunotherapy.Tryptase genotypes and HαT status might modify food allergy clinical presentation and biological features.